FLOOD MANAGEMENT OF THE CITARIK UPSTREAM RIVER, RANCAEKEK-CICALENGKA SUBDISTRICT, BANDUNG DISTRICT, WEST JAVA PROVINCE - Arsyad Pratama, Nudy
The rapid growth of the region by clearing land for settlements, agriculture, plantations and industry provides logical consequences for the management of the region's water resources, especially the issue of flood prevention. For example, the development of the area in Bandung District is very rapid, which is followed by changes in land use resulting in drainage capacity, especially the Citarik River. Flood events are very detrimental both economically and socially, that's what happened to the people in Rancaekek-Cicalengka. This research is intended to plan an infrastructure that can overcome floods caused by the overflow of the Citarik River such as embankments. The first stage of analysis is a hydrological analysis which is intended to determine the amount of flood discharge that flows in the river, then the next stage of hydraulic analysis is assisted by a model using HEC RAS 6.1 software, either 1 dimension or 2 dimensions. Based on the model, it will be found which river sections are experiencing runoff and the determination of the use of sheet pile embankments will be adjusted to the existing border space.